مفهوم البيئة ومكانتها في التشريعات الجزائرية - لكحل, أحمد (revue mofakir; No 07 (2011): مجلة المفكر, 2018)
الملخص : قد يتساءل البعض عن الصلة بين السياسة التشريعية لدولة من الدول في حماية قيمة معينة من قيم المجتمع والإدارة التنفيذية لتحقيق هذه الحماية، على أساس أن الأولى متعلقة بالتشريع والثانية بالتنفيذ، وهي سلطات مستقلة عن بعضها البعض، ولكن في حقيقة الأمر أثبت العمل أو وجود تشريعات على مستوى عال من الدقة والشمول لا قيمة له، إلا إذا كان التنفيذ والتطبيق لهذه القوانين محل عناية حتى تكتمل الحماية البيئية، وبالتالي لا محل للفصل بينهما . ولعل وجهة النظر هذه تظهر بوضوح الحماية القانونية للبيئة، فقد لجأ المشرع الجزائري لإصدار مجموعة كبيرة من التشريعات السابقة والحالية، ولكن تطبيقها وتنفيذها لم يكن بالمستوى المطلوب مما ترتب عليه ازدياد مجالات الاعتداء على البيئة دون أن تساعد التشريعات المتعددة على حمايتها . وانطلاقا من هذه الإشكالية تهدف الورقة إلى استعراض السياسة العامة للجماعات المحلية في حماية البيئة، مع توضيح العلاقة الجوهرية بين حماية البيئة من جهة والجماعات المحلية من جهة أخرى . وتتمحور حول مدى التأثير المتبادل بين العناصر الثلاث التشريع والهيئات المحلية والبيئة؟ وما هي أوجه التفاعل بينها؟ وما هي الصعوبات التي تحول دون تطبيقها الفعال، وبالتالي استمرار التخلف والتدهور البيئي ؟       Abstract: Some may wonder about the relation between the legislative policy of a state in protecting a particular value among diffrent values of the society and the role of the executive administaration in attaining this protection, on the basis of the affiliation of the first one to the legislation and the second one to the execution . However ,they are Independent authoreties one from the other, but in reality, work and the presence of legislations of a high level of accuracy and comprehensibility prooved that they have no value, only if the execution and the implimentation of these laws are put into consideration till the enviremental protection is fullfiled and therefore can not be dissociated. And perhaps this point of view shows clearly the legal protection of the environment, since the algerian legislator released lot of former and current legislations which had not been implemented and carried out at the requiered level . as a consequence there had been an increase in the areas of agressions on the enviroment ,without the ability of the diffrent legislations to help in protecting it. Starting from this problem, this paper aims to expose the general policy of local communities in the protection of the environment, and to clarify the essential relation between the protection of the environment on one hand, and local groups on the other hand. and focus on the extent of the mutual influence between the three elements of the legislation and local authorities and the environment, what are the aspects of interaction between them ? And what are the difficulties which prevent the effective implementation ?. and therefore, the persistence of underdevelopment and environmental degradation ?